Collaboration of Starbucks and Blackpink to Increase Purchase Intention - Felicia, Messy; Muharman, Deddy (MIMBAR : Jurnal Sosial dan Pembangunan, 2023)
The development of the times and the impact of globalization have made it easier for foreign cultures to enter Indonesia; one example is Korean culture. Korean Wave or Hallyu is a term often used to describe the phenomenon of Korean popular culture. Therefore, this research aims to determine the relationship between Starbucks and Blackpink Collaboration on interest in purchasing Blackpink special edition tumblers. The theory used in this research is the S-O-R theory. The method used is quantitative; this research uses a sampling technique using the Non-Probability Sampling method with a total sample of 97 respondents who are fans or knowing Blackpink and Starbucks in Indonesia. The research results show that the Blackpink special edition tumbler product collaboration variable (X) and the purchase intention variable (Y) have a strong relationship. The correlation coefficient value shows a positive number, which means there is a unidirectional relationship between the two variables.